PROFIL ANTIBODI ANTI-SARS-CoV-2 S1RBD (IgG) PASCA VAKSINASI COVID-19 PADA CIVITAS AKADEMIKA POLTEKKES KEMENKES BANJARMASIN - Dinna Rakhmina; Linda Yuliana (Husada Mahakam, 2022)
The first vaccination program started in early December 2020 and as of February 15, 2021, 175.3 million doses of the vaccine had been administered. Although the clinical trial data for the Covid-19 vaccine meets the WHO standard requirements, concrete evidence relating to the efficacy and effectiveness of the vaccine still needs to be researched and developed further. Therefore, there is still a lack of research and publications on the development of the Covid-19 vaccine in Indonesia, so this research will raise the issue of the extent to which factors of age, gender, ethnicity, history of Covid-19 infection, and vaccination dose affect the formation of antibodies after Covid vaccination. -19 in the Banjarmasin Ministry of Health Poltekkes academic community and the ability to protect against Covid-19 infection. The research is an analytical survey with a cross sectional design and as a sample is the academic community of Poltekkes Kemenkes Banjarmasin who have been vaccinated against Covid-19 stages I, II and III (booster). The method of determining antibody levels uses the ELISA principle plus supporting data through a questionnaire to explore data on the characteristics of the respondents. The results of measurements with ELISA obtained levels of Anti-SARS-Cov-2 S1RBD IgG antibodies which were grouped into 3 categories, namely: low (< 5 IU/mL) 3%, moderate (5 – 99 IU/mL) 8%, high (> 99 IU/mL) 89% and there is a significant value in terms of vaccination dose where the dose up to stage III (booster) is directly proportional to the increase in the level of antibodies formed. Keywords: Covid-19 Vaccination, Antibody Level, Elisa Method